2017
DOI: 10.3892/mco.2017.1520
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer effects of Bilberry anthocyanins compared with NutraNanoSphere encapsulated Bilberry anthocyanins

Abstract: Abstract. Rapidly accumulating laboratory and clinical research evidence indicates that anthocyanins exhibit anticancer activity and the evaluation of bilberry anthocyanins as chemo-preventive agents is progressing. It has previously been demonstrated that anthocyanins upregulate tumor suppressor genes, induce apoptosis in cancer cells, repair and protect genomic DNA integrity, which is important in reducing age-associated oxidative stress, and improve neuronal and cognitive brain function. Bilberry anthocyani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 29 publications
0
25
0
2
Order By: Relevance
“…It has been hypothesized that besides providing improved stability, encapsulation may favor intestinal absorption and metabolism of anthocyanins. Indeed, in vitro studies demonstrated that nanocomplexes with chitosan hydrochloride, carboxymethyl chitosan and β-lactoglobulin may favor the bioavailability of anthocyanins in a simulated gastrointestinal tract [ 120 ]; that bilberry anthocyanins encapsulated in liposomal micelles were more bioavailable at the cellular level in vitro; and that their efficacy as anticancer agents was significantly higher than that of non-encapsulated anthocyanins [ 121 ]. However, a recent paper by Mueller et al [ 122 ], in which the anthocyanins were encapsulated in whey proteins, demonstrated that this formulation had little effect on the stabilization of anthocyanins during intestinal passage, and increased the rate of degradation when compared to non-encapsulated anthocyanins.…”
Section: Anthocyanins In Foodmentioning
confidence: 99%
“…It has been hypothesized that besides providing improved stability, encapsulation may favor intestinal absorption and metabolism of anthocyanins. Indeed, in vitro studies demonstrated that nanocomplexes with chitosan hydrochloride, carboxymethyl chitosan and β-lactoglobulin may favor the bioavailability of anthocyanins in a simulated gastrointestinal tract [ 120 ]; that bilberry anthocyanins encapsulated in liposomal micelles were more bioavailable at the cellular level in vitro; and that their efficacy as anticancer agents was significantly higher than that of non-encapsulated anthocyanins [ 121 ]. However, a recent paper by Mueller et al [ 122 ], in which the anthocyanins were encapsulated in whey proteins, demonstrated that this formulation had little effect on the stabilization of anthocyanins during intestinal passage, and increased the rate of degradation when compared to non-encapsulated anthocyanins.…”
Section: Anthocyanins In Foodmentioning
confidence: 99%
“…Most studies have shown that the consumption of anthocyanin-rich food reduces the development of chronic diseases, including diabetes, cardiovascular diseases, atherosclerosis, arthritis, and cancers [ 21 , 22 , 23 , 24 ]. In addition, many in vitro and in vivo studies have also documented the beneficial effects of anthocyanins on lipid metabolism, oxidative stress, inflammation, hyperglycemia, and visceral fat accumulation and insulin signaling [ 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…En relación a esto, más de un estudio científico muestra que el extracto de arándano es el más eficaz para inhibir el crecimiento de células de leucemia humana HL60 y células de carcinoma de colon humano HCT116 in vitro. La evidencia de laboratorio y de investigación clínica que se está acumulando rápidamente indica que las antocianinas, presentes en el arándano, muestran actividad anticancerígena y la evaluación de las antocianinas de arándano como agentes de prevención química está progresando 16,17 .…”
Section: Metodologíaunclassified